A review of mechanical move sprinkler irrigation control and automation technologies - Kranz, W. L.; Evans, R. G.; Lamm, Freddie R.; O’Shaughnessy, S. A.; Peters, R. T. (My University, 2012)
Electronic sensors, equipment controls, and communication protocols have been developed to meet the growing interest in using center pivot and lateral move irrigation systems to deliver different irrigation depths to management zones based on previous production levels, soil texture, or topography. Onboard and field-distributed sensors can collect data necessary for real-time irrigation management decisions and transmit the information directly or through wireless networks to the main control panel or base computer. Equipment controls necessary to alter water application depth to meet the management criteria for relatively small management zones are now commercially available from irrigation system manufacturers and after-market suppliers. Communication systems such as cell phones, satellite radios, and internet-based systems are also available and allow the operator to query the main control panel or base computer from any location at any time. Selection of the communications system for remote access depends on local and regional topography and cost relative to other methods. Recent developments in the center pivot sprinkler industry have led to contractual relationships between after-market suppliers and irrigation system manufacturers that should support further development of technologies necessary to improve the management of water, nutrient and pesticide applications. Although the primary focus of this article is center pivot sprinkler irrigation, much of the discussion could also apply to lateral move sprinkler irrigation systems.
Keywords: Center pivot sprinkler; Distributed sensor networks; Site-specific irrigation; Variable rate irrigation; Wireless communication